Influence of the infiltrate density in the interstitium on the prognosis of primary glomerulonephritis - Božić, Dušan; Knežević, Violeta; Stražmešter Majstorović, Gordana; Petrović, Lada; Ćelić, Dejan; Ljubičić, Bojana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Development of inflammatory changes, fibrosis and loss of morphological structures of the interstitium have an important role in pathogenesis of primary glomerulonephritis, affecting the development, course and prognosis of the disease. The aim of this study was to determine the influence of changes in the interstitium on the prognosis of primary glomerulonephritis. Methods. The research included 216 patients suffering from different types of primary glumeronephritis treated at the Clinic for Nephrology and Clinical Immunology of the Clinical Center of Vojvodina, Serbia who were being monitored on average for 77.5 months. After determining on pathohistological diagnosis of the type of glomerulonephritis, renal changes in the interstitium were quantified. Numerical density in the tissue volume unit and structure of infiltrates of the interstitium were established by using the Weibel system (M42) incorporated into light microscope. Routine analyses were performed by using standard laboratory procedure. Results. During the research period the highest numerical density of infiltrates was verified in extracapillary glomerulonephritis (147,869 × mm-3), slightly less in membranoproliferative glomerulonephritis (116,800 × mm-3) and focal segmental glomerulosclerosis (96,147 × mm-3), and the least being in glomerulonephritis with minimal changes (11,416 × mm-3). In all types of glomerulonephritis, apart from glomerulonephritis with minimal changes, there was a significantly (p < 0.0005) higher numerical density and incidence of infiltrate cells in relation to the control group. By comparing the numerical density of infiltrates of all cells to the parameters of renal function, a significant (p < 0.01) correlation of these phenomena was established. In order to get a better insight into the speed of progression of renal failure by setting a numerical limit of the density of infiltrates < 100,000 / > 100,000 cells/mm3, regardless of the type of glomerulonephritis, a prognostic predictor was established on the basis of which the patients with lower infiltration of the interstitium had significantly (p < 0.005) lower progression of renal failure. Conclusion. Density of infiltrates in the interstitium in primary glomerulonephritis is an important early prognostic predictor of progression of renal failure.